2017
DOI: 10.1128/jvi.01309-17
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Human Endogenous Retrovirus Type K to Reverse Transcriptase Inhibitors

Abstract: Human endogenous retroviruses (HERVs) make up 8% of the human genome. The HERV type K (HERV-K) HML-2 (HK2) family contains proviruses that are the most recent entrants into the human germ line and are transcriptionally active. In HIV-1 infection and cancer, HK2 genes produce retroviral particles that appear to be infectious, yet the replication capacity of these viruses and potential pathogenicity has been difficult to ascertain. In this report, we screened the efficacy of commercially available reverse transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 61 publications
(84 reference statements)
0
51
1
Order By: Relevance
“…Strand-specific accumulation of pericentromeric transcripts in MRC5 cells prompted us to examine their potential amplification, which could be driven by Pol II 29,31,32 or by RTs of either cellular (such as TERT, shown for HSAT2 40 ) or retroviral 41,42 origin. We found that Pol II inhibitor DRB and, to a lesser extent, actinomycin D (ActD; a pleiotropic polymerase inhibitor) strongly blocked accumulation of HSAT2, ACRO1 and HERV-Kenv, along with IFNβ mRNA used as an internal control (Fig.…”
Section: Cell-to-cell Transmission Of Ews Ev Rnasmentioning
confidence: 99%
See 1 more Smart Citation
“…Strand-specific accumulation of pericentromeric transcripts in MRC5 cells prompted us to examine their potential amplification, which could be driven by Pol II 29,31,32 or by RTs of either cellular (such as TERT, shown for HSAT2 40 ) or retroviral 41,42 origin. We found that Pol II inhibitor DRB and, to a lesser extent, actinomycin D (ActD; a pleiotropic polymerase inhibitor) strongly blocked accumulation of HSAT2, ACRO1 and HERV-Kenv, along with IFNβ mRNA used as an internal control (Fig.…”
Section: Cell-to-cell Transmission Of Ews Ev Rnasmentioning
confidence: 99%
“…5c). The RT inhibitors 3'-Azido-3'-deoxythymidine (AZT/zidovudine; an inhibitor of HIV, HERV-K and L1-encoded RT activities 42,43 ) and nevirapine (NVP) had moderate effects, with AZT being more efficient in reducing levels of HSAT2, HERV-Kenv and ACRO1 by ~1.6 and 2.5-fold, respectively ( Fig. 5c); the observed reduction in IFNβ mRNA levels could be due to a decrease in repeat RNAs and diminished antiviral response under these conditions.…”
Section: Cell-to-cell Transmission Of Ews Ev Rnasmentioning
confidence: 99%
“…The current evidence, taken from in vitro studies, suggests that HERV type K is susceptible to most members of a class of ARVs called nucleoside reverse transcriptase inhibitors (NRTIs; 38,39), but is relatively resistant to ARVs from the class protease inhibitors (PIs; [38][39][40][41]. Evidence for in vitro efficacy of non-nucleoside reverse transcriptase inhibitors (NNRTIs) and integrase inhibitors (INSTIs) is mixed (38,39).…”
Section: Mechanismsmentioning
confidence: 99%
“…While serum creatine kinase (total CK) levels dropped coincident with treatment, ''clinical courses were not significantly altered'' (48). This trial utilized an ARV that has excellent penetrance into the CNS (49) and has been reported to be active in vitro against HERV (38,39); however, the trial design was flawed in that it enrolled a very small number of PALS, followed them for variable amounts of time, and used unclear clinical outcome measures. The second ARV trial was a double-blind trial that randomized 46 PALS to either the protease inhibitor indinavir or placebo for 9 months.…”
Section: Trialsmentioning
confidence: 99%
See 1 more Smart Citation